Numerical analysis of interface crack problem in composite plates jointed with composite patch - Cetisli, Fatih; Kaman, Mete O. (Techno-Press, 2014)
Stress intensity factors are numerically investigated for interfacial edge crack between two dissimilar composite plates jointed with single side composite patch. Variation of stress intensity factor under Mode I loading condition is examined for different material models and fiber orientation angles of composite plates and patch. ANSYS 12.1 finite element analysis software is used to obtain displacements of crack surfaces in the numerical solution and repaired plates are modeled in three dimensions. Obtained results are presented in the form of graphs. It is found that fiber orientation angle of composites is an effective parameter on interfacial stress intensity factor.
Keywords: interface crack; composite patch; stress intensity factor; finite element method